Role of Hepcidin in Pediatric Chronic Kidney Disease with Anemia - Aras, Jusli; Kardani, Astrid Kristina; Soemaryo, Ninik Asmaningsih; Prasetyo, Risky Vitria; Noer, Mohammad Sjaifullah; Ugrasena, I Dewa Gede (Green Medical Journal, 2021)
Introduction: Anemia is a frequent complication of chronic kidney disease (CKD) in children and it causes an increase in morbidity, mortality and accelerates the rate of progression of CKD. Inflammation and impaired kidney clearance increase plasma hepcidin, inhibiting duodenal iron absorption and sequestering iron in macrophages. However, the role of hepcidin in increasing the risk of anemia in children with CKD is still uncertain. This study aimed to investigate the association between hepcidin levels and anemia in children with pre-dialysis CKD. Methods: A cross-sectional study was conducted at Dr. Soetomo Academic Hospital from December 2018 to February 2019. Children with pre-dialysis CKD were enrolled in this study. The subject had no history of erythropoietin administration and blood transfusion 3 months before the blood sample were withdrawn. A complete blood count, ferritin serum, transferrin saturation (TSAT) and hepcidin serum were performed. The correlations between Hepcidin and ferritin level, between ferritin level and anemia, and between TSAT and anemia were analyzed using Spearman correlation and the Mann-Whitney test. Results: A total of 47 children, 27 boys and 20 girls, ranged in age from 3 months to 18 years old. There was a significant correlation between hepcidin and ferritin levels (p=0.006) and the value of the Spearman correlation was r=0.392. While the correlation between ferritin level and anemia showed a significant result, p=0.001. However, TSAT did not show any significant correlation with anemia (p=0.230). Conclusion: There was an indirect association between hepcidin level and anemia by increasing ferritin level that induces anemia in pre-dialysis CKD children.